Some issues for the teaching of writing (2002)
In this article the definition of writing as a means and as an end is analyzed in order to raise some concerns about the teaching of writing at different schools in general. From this definition I question other important issues that ultimately affect our students¿ writing production. These have to deal with the use of writing in the mother language, writing activities in the textbooks, the realistic nature of the writing tasks, the other language skills input, and the production of texts. The article pretends to raise awareness in the teaching of writing by taking into account what is implied in the writing skill so teachers can be more attentive in the selection of written tasks for their students.